2019
DOI: 10.1101/833251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Sparse Deep Learning Approach for Automatic Segmentation of Human Vasculature in Multispectral Optoacoustic Tomography

Abstract: Multispectral Optoacoustic Tomography (MSOT) resolves oxy-(HbO2) and deoxy-hemoglobin (Hb) to perform vascular imaging. MSOT suffers from gradual signal attenuation with depth due to light-tissue interactions: an effect that hinders the precise manual segmentation of vessels. Furthermore, vascular assessment requires functional tests, which last several minutes and result in recording thousands of images. Here, we introduce a deep learning approach with a sparse UNET (S-UNET) for automatic vascular segmentatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Furthermore, in quantifying the features of vascular modeling seen in skin vascular diseases, the vasculature network in the images have to be manually segmented which is tedious and time-consuming, especially in deeper depths and large functional data sets. Chlis et al reported a specialized deep learning method, the sparse UNET (S-UNET) which is the leading deep network in image segmentation, to automatically segment vascular networks in MSOT images to address this challenge [48]. This method was able to segment both arteries and veins from unconstructed MSOT acquisitions precisely, even in signal attenuated depths from images of two wavelengths: 850 nm (maximum absorption of HbO 2 ) and 810 nm (isosbestic point of HbO 2 and Hb).…”
Section: Vasculature Imagingmentioning
confidence: 99%
“…Furthermore, in quantifying the features of vascular modeling seen in skin vascular diseases, the vasculature network in the images have to be manually segmented which is tedious and time-consuming, especially in deeper depths and large functional data sets. Chlis et al reported a specialized deep learning method, the sparse UNET (S-UNET) which is the leading deep network in image segmentation, to automatically segment vascular networks in MSOT images to address this challenge [48]. This method was able to segment both arteries and veins from unconstructed MSOT acquisitions precisely, even in signal attenuated depths from images of two wavelengths: 850 nm (maximum absorption of HbO 2 ) and 810 nm (isosbestic point of HbO 2 and Hb).…”
Section: Vasculature Imagingmentioning
confidence: 99%
“…The blood vessel visualization using multispectral optoacoustic tomography is considered in Ref. [11]. As an alternative to manual segmentation of the obtained images, the authors propose the use of "sparse-UNET".…”
Section: Introductionmentioning
confidence: 99%